The Role of Branding in Marketing Tourism “Study of Royal Karbala hotel” (The Peerian Journal, 2024)
The study shows that the brand plays a pivotal role in enhancing the tourist attractiveness of luxury hotels, as it reflects the quality of services and contributes to building customer confidence. The brand is a strategic tool with a significant impact on tourism performance. The study confirms the importance of investing in brand building as a means of attracting customers and enhancing their loyalty, which supports the sustainable growth of luxury hotels. The statistical results showed that participants evaluate the brand positively, with averages ranging between 3.92 and 4.36, reflecting the importance of the brand in tourists’ decisions. Descriptive statistics show that tourists associate brands with quality of service and distinctive lodging experiences, which are decisive factors in their choice of destination. They also showed that while brand perception is an independent factor influencing tourists' decisions, it needs to be supported by other factors such as reputation and customer experience to improve its overall impact. The results showed that a strong brand reinforces tourists' decision-making, especially when it is in line with their expectations regarding service quality. The importance of focusing on enhancing the hotel experience by providing innovative and exceptional service is another key finding of the study.